Effects of once‐weekly dulaglutide on kidney function in patients with type 2 diabetes in phase II and III clinical trials. Issue 3 (24th November 2016) - Tuttle, Katherine R.; McKinney, T. Dwight; Davidson, Jaime A.; Anglin, Greg; Harper, Kristine D.; Botros, Fady T.
Abstract : Dulaglutide is a once‐weekly glucagon‐like peptide‐1 receptor agonist approved for the treatment of type 2 diabetes (T2D). Integrated data from 9 phase II and III trials in people with T2D (N = 6005) were used to evaluate the effects of dulaglutide on estimated glomerular filtration rate (eGFR [Chronic Kidney Disease Epidemiology Collaboration]), urine albumin‐to‐creatinine ratio (UACR) and kidney adverse events (AEs). No significant differences in eGFR were observed during treatment for dulaglutide vs placebo, active comparators or insulin glargine (mean ± standard deviation values: dulaglutide vs placebo: 87.8 ± 17.7 vs 88.2 ± 17.9 mL/min/1.73 m 2, P = .075; dulaglutide vs active comparators: 89.9 ± 16.7 vs 88.8 ± 16.3 mL/min/1.73 m 2, P = .223; and dulaglutide vs insulin glargine: 85.9 ± 18.2 vs 83.9 ± 18.6 mL/min/1.73 m 2, P = .423). Lower UACR values were observed for dulaglutide vs placebo, active comparators and insulin glargine (at 26 weeks, median [Q1‐Q3] values were: dulaglutide vs placebo: 8.0 [4.4‐20.4] vs 8.0 [4.4‐23.9] mg/g, P = .023; dulaglutide vs active comparators: 8.0 [4.4‐21.2] vs 8.9 [4.4‐27.4] mg/g, P = .013; and dulaglutide vs insulin glargine: 8.9 [4.4‐29.2] vs 12.4 [5.3‐50.5] mg/g, P = .029). AEs reflecting potential acute renal failure were 3.4, 1.7 and 7.0 events/1000 patient‐years for dulaglutide, active comparators and placebo, respectively. In conclusion, dulaglutide treatment of clinical trial participants with T2D did not affect eGFR and slightly decreased albuminuria.